Isomerisation of cyclohexane to methylcyclopentane over Pt/SO4 2--ZrO2 catalyst - Sugeng, Triwahyono; Aishah, Abdul Jalil; Halimaton, Hamdan (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/